Stigmatizing attitudes toward mental disorders among non-mental health nurses in general hospitals of China: a national survey - Li, Li; Lu, Shurong; Xie, Chunyan; Li, Yamin (Frontiers in Psychiatry, 2023)
Background: Negative attitudes of nurses towards mental disorders have been reported in various countries. Nurses’ stigmatising attitudes can harm patients with mental disorders (PWMD), thereby delaying the provision of help to patients and leading to decreased quality of care. Objective: This study aimed to assess the attitudes of Non-mental Health Nurses (NMHNs) in general hospitals in China towards the stigma of PWMD and determine the factors influencing them to provide a basis for future development and testing of appropriate and culturally adapted interventions to reduce it. Methods: A cross-sectional survey of NMHNs in general hospitals were conducted. A self-designed WeChat-based questionnaire was used that included demographic information about the need for training on mental health issues. Participants were provided with a vignette of a depression case with suicidal thoughts. The Depression Stigma Scale (DSS) and Social Distance Scale (SDS) were used to assess attitudes towards mental disorders. Nine questions on the adequacy of knowledge about anxiety and depression and the current status of scale use were used to assess the current status of training needs for mental disorders. Descriptive analysis, chi-square test and multivariate logistic regression were used for the table. Results: A total of 8,254 nurses in non-mental health professions participated in this study. The mean DSS score of NMHNs was (17.24 ± 6.700), and the SDS score was (10.34 ± 3.154). The total detection rate of stigma amongst the survey respondents was 13.40%. Multivariate logistic regression showed that age between 30–39 years , 4 years of work experience and above , bachelor’s degree, adequate psychological knowledge , full knowledge of communication with patients with anxiety and depression and the need to acquire skills to identify anxiety and depression were the influencing factors associated with stigma. Conclusion: Stigmatising attitudes towards PWMD exist among NMHNs in general hospitals in China. Thus, more mental health education programs for NMHNs are needed. Factors associated with higher morbidity stigma can be used to develop appropriate interventions to improve NMHNs’ stigmatising attitudes and provide better quality care to PWMD.